Sustainability indicators for salmon aquaculture - Amundsen, Vilde Steiro (Data Brief, 2018)
In this paper, we present and describe data comprising indicators of sustainability, collected from eight of the major certification schemes for salmon aquaculture and categorized according to the topics covered by each. These indicators cover most aspects of aquaculture production, including biotic and abiotic effects, feed, emission and waste, fish health and welfare, social assurance, and respect for native culture. In addition to being published in its entirety as supplementary material alongside this article, the data is available through a searchable database on the SustainFish project site: https://sustainfish.wixsite.com/sustainfishproject/search-indicator-database.